The Queer Fantasies of the American Family Sitcom - Pugh, Tison (Rutgers University Press, 2021)
The Queer Fantasies of the American Family Sitcom explores how the fantasies of genre, marketing, and children can never fully cloak the queerness lurking within the plucky families designed for American viewers’ comic delight. Queer readings of family sitcoms demolish myths of yesteryear, demonstrating the illusion of American sexual innocence in television’s early programs and its lasting consequences in the nation’s self-construction, as they also allow fresh insights into the ways in which more recent programs negotiate new visions of sexuality while indebted to previous narrative traditions. Tison Pugh thoroughly explores six specific family sitcoms to illustrate how issues of sexuality intersect with other critical concerns of their respective periods and cultures.